Pasang In Sinrilik Concervation Effort Makassar Culture - Subair, Ahmad (Sean Institute, 2025)
Cultural heritage, particularly the traditional arts of Sinrilik and Pasang among the Bugis-Makassar people, has important philosophical and moral values. However, these two arts are increasingly marginalised among Generation Z in Paccinongang Village, Gowa Regency, who are more exposed to global culture. On the other hand, Generation Z also faces mental health challenges such as stress and anxiety due to academic and social pressures. This qualitative research with an ethnographic approach aims to: (1) analyse the cultural meaning of Sinrilik and Pasang , (2) identify their potential as innovative media for Generation Z's mental health, and (3) design revitalisation strategies. Through observation and in-depth interviews, this study found that the reflective values in Sinrilik and the moral messages in Pasang have a calming effect and can serve as guidelines for life. In response, the SIPAS (Sinrilik and Pasang) Programme was designed with a participatory approach involving local artists, community leaders, and Generation Z. The programme, which includes training, interactive performances, and digital documentation, has succeeded in increasing Generation Z's interest and understanding of their cultural heritage, while reducing anxiety levels and strengthening social cohesion. This research concludes that integrating traditional art preservation with a mental health approach through adaptive and participatory strategies can create sustainable solutions for the future of culture and well-being. This study concludes that integrating the preservation of traditional arts with a mental health approach through adaptive and participatory strategies can create sustainable solutions for the cultural future and psychological well-being of Generation Z.